Management of district health centers in Iloilo City - Cofreros, Dicof D.; Marbebe, Ma. Redli M.; Melancio, Grace C.; Padilla, Aizel M.; Pagunsan, Josette Sharyn C.
District Health Centers provide health services within its area of responsibility and offers higher level of care compared to Barangay Health Stations. The study aims to describe the status of District Health centers in Iloilo City and the management of health services in these centers. It also provides an assessment of the effectiveness and efficiency of the delivery of health services. The District Health Centers in the study include the Mandurriao DHC, City Proper DHC, Arevalo District health Unit, Jaro 1 health Center City Proper Office and La Paz District Health center. The Senior Medical Officer heads the district health center and assisted by a staff composed of nurses, midwives, and Volunteer Barangay Health Workers (VBHW). Funding comes primarily from the City Government. Other sources are Philhealth, the local Government Units (LGUs) and Non-Government Organizations (NGOs). Each center has an examining bed, examining table, refrigerator, and medicine cabinet. among others are computer and/or typewriter, ceiling fans and electric fans, fax machine and telephones, air condition units and a DVD player. medical equipments in the centers include syringes, stethoscope, thermometers and sphygmomanometers. They also have weighing scales, bathroom scales and lever tape scales. Other equipments are electric boilers, flash lights, sterilizer, microscope, dressing carts, autoclave machines and many others. District Health Centers experience problems in the shortage of finances, medical equipments and to the supply of medicines and facilities. They also lack enough space to accommodate their parents. These problems arise due to the fact that there is an insufficient budget given to them by the city government and to the minimal donations that they get from other organizations. The level of effectiveness of the delivery of health services by DHC's is found to be rated "very satisfactory" while its efficiency was rated "4" in a range of 1-5 with 5 as the highest. In view of the problems determined by the researchers, the group recommends to develop a two-way communication scheme to address the issue on policies that are not being carried out or implemented in these District health centers. It is also recommended to conduct a review on the policies regarding the provision of the needs of the District Health Centers and make its provision be faster so as not to delay the services which will be delivered to the citizens. District health centers are the avenue for protecting and preserving the lives of every individual in every district and they are expected to deliver these services in high quality and efficiency thus, the problems addressed by the researchers must be acted upon in the fastest possible way.